Assembly of Mesoporous Metal–Organic Framework Templated by an Ionic Liquid/Ethylene Glycol Interface. Issue 11 (15th May 2015) - Sang, Xinxin; Zhang, Jianling; Peng, Li; Liu, Chengcheng; Ma, Xue; Han, Buxing; Yang, Guanying
Abstract We propose a facile room‐temperature synthesis of a metal–organic framework (MOF) with a bimodal mesoporous structure (3.9 and 17‐28 nm) in an ionic liquid (IL)/ethylene glycol (EG) mixture. The X‐ray diffraction analysis reveals that MOF formation can be efficiently promoted by the presence of the EG/IL interface at room temperature. The MOFs with mesoporous networks are characterized by SEM and TEM. The formation mechanism of the mesoporous MOF in EG/IL mixture is investigated. It is proposed that the EG nanodroplets in the IL work as templates for the formation of the large mesopores. The as‐synthesized mesoporous metal–organic framework is an effective and reusable heterogeneous catalyst to catalyze the aerobic oxidation of benzylic alcohols.